Design details for health making the most of interior design's healing potential - Leibrock, Cynthia (Wiley, 2000)
"In design details for health, she offers specific design details that can improve patient outcomes by returning authority to the patient, along with fascinating case studies and research demonstrating the positive role design details can play in reducing healthcare costs. Practical and inspiring, this innovative book is essential reading for architects, interior designers, facility managers, and healthcare professionals." -- Provided by publisher